(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The 21st century has witnessed a significant transformation in environmental politics, driven largely by the growing influence of international institutions. This study examined the role of global organizations such as UNEP, IPCC, UNFCCC, World Bank, CBD, and UNCCD in shaping environmental governance. Using a descriptive and analytical research design based on secondary data from 2010 to 2024, the study analyzed institutional contributions in terms of policy formulation, financial assistance, monitoring mechanisms, and international cooperation. The findings revealed that international institutions have successfully expanded global participation, with over 190 countries engaged in environmental agreements, and have established key frameworks such as the Paris Agreement and biodiversity conventions. However, the study also identified a significant gap between political commitments and scientific requirements, as current emission reduction targets (7–10%) fall short of the IPCC-recommended 43% needed to limit global warming to 1.5°C. Additionally, while climate finance and cooperative mechanisms have improved, inequalities in economic and technological capacities continue to hinder effective implementation, particularly in developing countries. The study further highlighted the influence of geopolitical power dynamics, where developed countries dominate climate finance contributions and decision-making processes. Overall, the research concluded that although international institutions play a crucial role in advancing environmental politics, their effectiveness is constrained by implementation gaps, insufficient funding, and structural inequalities. Strengthening enforcement mechanisms, ensuring equitable participation, and enhancing financial and technological support are essential for improving global environmental governance.